2018
DOI: 10.1016/j.jnma.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Public Attitudes and Knowledge About Youth Sports Participation and Concussion Risk in an Urban Area

Abstract: Background: Every year, millions of children in the United States participate in youth full-contact sports, which carry concussion risks—the long-term sequelae of which are not well understood. We examined the attitudes and knowledge of adults in Chicago about youth sports participation, concussion risk, and whether physicians should counsel against youth participation in full-contact sports. Methods: An anonymous paper survey featuring 13 attitudinal, 13 demographic, and 9 knowledge questions was distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Moreover, in all studies of current high school and collegiate athletes, earlier age of first exposure to contact and collision sports has not been associated with worse neurocognitive functioning, subjectively-experienced symptoms, or postural control during preseason baseline testing (12-16, 18, 19), or worse clinical outcome following concussion (17). Considering the literature more broadly, separate from the issue of age of first exposure to football, results from 7 studies (33-38) 2 have observed that men who played high school football are not at increased risk for later-in-life neurodegenerative disease (36,37), and they do not report greater mental health problems in their 20s (33, 34), during middle age 2 , or during older adulthood (35,38). In conclusion, the results of this study suggest that earlier age of first exposure to football is not associated with worse brain health in middle-aged and older adult men who played high school football.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in all studies of current high school and collegiate athletes, earlier age of first exposure to contact and collision sports has not been associated with worse neurocognitive functioning, subjectively-experienced symptoms, or postural control during preseason baseline testing (12-16, 18, 19), or worse clinical outcome following concussion (17). Considering the literature more broadly, separate from the issue of age of first exposure to football, results from 7 studies (33-38) 2 have observed that men who played high school football are not at increased risk for later-in-life neurodegenerative disease (36,37), and they do not report greater mental health problems in their 20s (33, 34), during middle age 2 , or during older adulthood (35,38). In conclusion, the results of this study suggest that earlier age of first exposure to football is not associated with worse brain health in middle-aged and older adult men who played high school football.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been growing public health concerns regarding the long-term effects of youth football participation. Among the general public, 54% of surveyed adults would not allow their child to play youth football ( 2 ). Among pediatricians queried, 77% would not allow their child to play youth football ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent survey, 46% of people stated they would not let their hypothetical 10-year-old son play American football. 23 Conversely, participation in sports has shown benefits in movement skills, physical competencies, social skills, social behaviors, self-esteem, proschool attitudes, academic development, and cognitive development. 2 Earlier epidemiological studies showed concussion rates in high school football ranging from 3.66% 18 to 5.6% 9 and an estimated incidence of 43,200 to 67,200 concussions annually.…”
Section: Concussionmentioning
confidence: 99%
“…Many have suggested that the public’s understanding and confidence in science has eroded in recent years due to development of the Internet and the growing influence of social media (Lewandowsky et al, 2012; Peters, Tartari, Lotfinejad, Parneix, & Pittet, 2018; Wang, McKee, Torbica, & Stuckler, 2019). In fact, it has been shown that the vast majority of individuals are obtaining information on concussion and CTE from the news and sports media with far fewer obtaining this information from medical health care sites or directly from physicians (Taranto et al, 2018). Studies have shown that the quality of information on these topics varies widely across websites, increasing the potential to perpetuate many of the ongoing misperceptions (Ahmed, Sullivan, Schneiders, & McCrory, 2012).…”
Section: Development Of the Believer Versus Denier Mentalitymentioning
confidence: 99%